Combined diffusion and perfusion index maps from simplified intravoxel incoherent motion imaging enable visual assessment of breast lesions - Petra Mürtz; Alois M. Sprinkart; Wolfgang Block; Julian A. Luetkens; Ulrike Attenberger; Claus C. Pieper (Scientific Reports)
Abstract The aim was to evaluate visual breast lesion assessment using single binary index maps (IDf) in comparison to the use of combined regions of interest (ROI) analysis of estimated diffusion coefficient (D′) AND perfusion fraction (f′), which proved to be the best method in a previous simplified intravoxel incoherent motion DWI, if diffusion-weighted imaging (DWI) is used as stand-alone tool. IDf, was constructed voxel-wise from cut-off values of D′ and f′. The cut-off values, the data of 105 malignant and 86 benign lesions and the ROIs were re-used. For visual assessment, IDf was displayed as two-colour b800 overlay with red representing “malignant” and green “benign” voxels. A lesion was rated as “malignant”, if a red hot spot was found within translucent hyperintensity on b800, otherwise as “benign”. Intraindividual comparison of quantitative analysis and visual assessment of IDf showed comparable accuracy, both to each other and to combined ROI-analysis of D′ and f′ maps (0.927 vs. 0.937, p = 0.157, and 0.921 vs. 0.937, p = 0.157, respectively). Thus, visual assessment of IDf can replace combined ROI analysis of D′ and f′ without loss in accuracy enabling a considerable facilitation in clinical routine.